Is Halldór Laxness the Author of Fóstbræðra saga? On the Author Function, Intertextuality, Translation, and a Modern Writer’s Relationship with the Icelandic Sagas - Ástráður Eysteinsson (Scandinavian-Canadian Studies, 2019)
ABSTRACT: Asking the titular question entails considering different concepts of authorship, from the modern sense of the term to Michel Foucault’s idea of the “author function,” as well as considering Halldór Laxness’s connection with the Icelandic sagas, in terms of his reception, editing, and rewriting/translation of them. The context of Halldór’s contemporary Iceland is also important, specifically the prevailing perceptions of the sagas. This article explores the interrelationship between Fóstbræðra saga and Halldór’s Gerpla through intertextuality and, ultimately, Halldór’s role in the contemporary reception of Fóstbræðra saga. The article was originally published in the journal Skáldskaparmál: Tímarit um íslenskar bókmenntir fyrri alda (1990). It has been slightly revised for republication in the author’s book, Orðaskil: Í heimi þýðinga (2017) and for this translation, which has been produced in collaboration with the author.